Assessment of the mechanical properties of peruvian Stipa Obtusa fibers for their use as reinforcement in composite materials - Candiotti, Sergio (2020)
This paper presents the study of the mechanical properties of technical fibers extracted from the Stipa Obtusa grass considering three different alkali treatment times, 1.5, 3 and 5 h; additionally, fiber/matrix compatibility is evaluated via the single fiber fragmentation test, and the best treatment in terms of mechanical properties and compatibility is used to test the effect of gage length, strain rate and cyclic deformation. Result shows that mechanical properties increase with treatment time until a maximum (strength similar to 569 MPa, modulus similar to 28 GPa and strain 0.026), and afterwards decreases; furthermore, strength and strain decreases as the fiber length increases; while, the strain rate's effect is negligible unless at very low speed, and a cyclic deformation leads to an increase of the modulus (similar to 13%). It can be concluded that fibers extracted from the Stipa Obtusa show potential and can compete with commercial natural fibers as a reinforcement in polymeric matrix composites.